GnRH agonists to sustain the luteal phase in antagonist IVF cycles: a randomized prospective trial - Francesco M. Fusi; Claudio M. Brigante; Laura Zanga; Mario Mignini Renzini; Chiara Bosisio; Rubens Fadini (BMC, 2019)
Abstract Background The addition of a GnRH analogue to the luteal phase in in vitro fertilization programs has been seldom proposed due to the presence of GnRH receptors in the endometrium. The aim of the study was to evaluate the effect of triptorelin addition in short antagonist cycles, compared to cycles where the only supplementation was progesterone. Methods The primary objective of this study was the study of the effect of Triptorelin addiction during the luteal phase on the live birth rate. Secondary objectives of efficacy were pregnancy rates and implantation rates, as well as safety in terms of OHSS risks. The study was a prospective, randomized, open study, performed in two independent Centers from July 2013 to October 2015. Patients were divided into three groups: a) Regular antagonist protocol, with only luteal progesterone; b) Antagonist protocol with luteal triptorelin as multiple injections, c) Antagonist protocol with luteal triptorelin as single bolus. Descriptive statistics were obtained for all the parameters. Mean and standard deviation were used for all quantitative parameters. Differences between percentages were studied using Chi-square test generalized to the comparison of several proportions. Results A total number of 1344 patients completed the study, 786 under the age of 35 years, and 558 over 35 years. It was observed an increase of positive HCG results, Clinical pregnancy rates and Delivery rates when triptorelin was added in the luteal phase, irrespective whether as a single bolus or five injections. This increase was statistically significant both for pregnancy rates and delivery rates. The statistic difference between pregnancies and deliveries obtained with or without luteal triptorelin reached p < 0,01. No increase of OHSS risk was observed. Conclusions From this large study it appears that the concept of luteal phase supplementation should be revisited. From our study it appears that triptorelin addition to the luteal phase of antagonist cycles, either as a single bolus or using multiple injections, is a good tool to optimize ART results. Trial registration The study was approved by the Ethics Committee of Provincia di Bergamo (n 1203/2013).